Review of William Paley, Natural Theology, edited with an introduction and notes by Matthew D. Eddy and David Knight - Branch, Glenn (Sophia, 2009)
Matthew D. Eddy and David Knight’s new edition of William Paley’s Natural Theology deserves to become the standard scholarly edition of what is a historically, theologically, and philosophically important work, despite a certain neglect of philosophical issues on the part of the editors.